Comparative analyses on the chemical compostion, phytochemcimal and antioxidant properties of selected milled varieties (finger and pearl millet) - Nassarawa, Sanusi Shamsudeen; Sulaiman, Salamatu Ahmad (International Journal of Food Sciences, 2019)
Purpose: Millet is a major food source in the arid and semi-arid parts of the world especially among people with low socio-economic status. It is a good source of energy, protein, minerals, dietary Fibre, fatty acid, amino acid (especially sulphur containing amino acid), phytochemicals and a good source of antioxidant. Methods: The millet varieties were obtained from the central market in Katsina state, Nigeria. The millet varieties (finger and pearl millet) were cleaned by washing in water, de-watered, sun dried, milled into flour and stored in sealed polythene bags. Standard method were used to determine the phytochemical, atomic absorption spectrometer, amino acid profile was determined spectrometically using a gas chromatography (GC), antioxidant property was measured by determination of free radical scavenging ability (DPPH,FRAP and ABTS) and data was analyzed by one way analysis of variance (ANOVA) using SPSS (16.0) software. The result obtained from studied millet varieties showed the fatty acid profile contain more than 70% unsaturated fatty acid. Amino acid profile showed the presence of essential amino acid of nutritional importance (especially the sulphur containing amino acids). Results: The results obtained from the studied millet varieties showed a protein content level within the range of (10.09%-10.85%), fat content level between the range (2.76%-4.43%), carbohydrate, fat and ash content between the range (71.56% - 73.18%), (2.23% - 3.24%) and (0.86% - 1.94%) respectively. The mineral composition showed it contained mineral elements of health importance, such as; phosphorus, calcium, potassium, sodium and magnesium as well as other minor elements such as copper, manganese, zinc and iron. Phytochemical analyses showed the presence of plant chemical such as; tannin, terpenoid, alkaloid, cardiac glycoside, saponin, oxalate, phytate, flavonoids and total phenol. Antioxidant analyses showed they possess ability to serve as reducing agent hence a rich source of antioxidant of health importance. Unique contribution to theory, practice and policy: The study revealed a high nutritional quality and possible therapeutic effect of the studied millet varieties which are locally sourced and relatively cheaper source of food for a teeming population like ours.